Startups and Effective Corporate Governance Models Proposed by the RA Legislation - Avetisyan, Vahram (Bulletin of Yerevan University C: Jurisprudence, 2021)
The article is devoted to identifying problems and presenting relevant solutions related to the definition of control systems, the role of a shareholder agreement in corporate governance, corporate conflicts, selfdefense of corporate rights, the choice of a corporate governance model for a company, as well as the choice of the most preferred form of legal entity for start-up companies offered by the RA legislation.